Budgetary participation, budget emphasis, and information asymmetry, on the incidence of budgetary slack (Study in Kampar district Government on education) - Erianti Sawitri; Raja Adri Satriawan Surya; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to find empirical evidence to support the notion that there are significant between budget participation, budget emphasis and information asymmetry on the incidence of budgetary slack in Kampar District Government on education.In this study, the samples taken were 140 people from 35 regional work units (on education) which consists of the Chief on education, public and officialdom sub-section, sub-section program planning, and finance sub-sections, which are involved in the preparation of the budget on education district government Kampar. Data collected through direct observation and surveys obtained by means of the distribution of questionnaires to the respondents. This study used multiple linear regression analysis model (multiple linear regression).The results showed that budget participation, budget emphasis and information asymmetry affect the budgetary slack.budgetary participation variables significantly affect the incidence of budgetary slack. Thus, participation budget the greater cause budgetary slack is the greater. The target budget is used as a measure of performance of subordinates, and / or the presence of monetary incentives such as bonuses, raises budget emphasis. Information asymmetry increases in the budgeting process, it will trigger increased budgetary slack anywayKeyword: Budgetary Participation, Budget Emphasis, Information Asymmetry, and Budgetary Slack.